Binding kinetics of blueberry pectin-anthocyanins and stabilization by non-covalent interactions. (February 2020) - Koh, Jeewon; Xu, Zhimin; Wicker, Louise
Abstract: The effect of pectin composition on the binding selectivity to anthocyanins was investigated by Langmuir isotherms with two blueberry pectins, water soluble fraction (WSF) and chelator soluble fraction (CSF). Adsorption was four times higher between CSF and anthocyanins, than WSF and anthocyanins. Higher adsorption was attributed to the more linear, more negatively charged homogalacturonan region of CSF, compared to the more branched, neutral sugar rich WSF. The CSF binding sites ( q m a x ) to anthocyanins were estimated at 1413–1904 μg/mg pectin, which was about eight times higher than WSF binding sites. No difference was observed in binding affinity ( K L ) among blueberry pectins. WSF, rich in neutral sugar side chains, showed lower and more variable interaction with anthocyanins. Binding studies also showed that blueberry pectin-anthocyanins adsorption was highest at pH 3.0 and lowest at pH 4.0. Increasing concentration from 25 to 200 mM citrate-phosphate (CP) weakened the pectin-anthocyanins interaction between pH values 3.0 and 4.0. However, no significant difference in binding was observed at pH 2.6 with increasing CP. As pH values changed from 4.0 to more acidic pH, electrostatic interaction decreased while hydrophobic interactions increased between blueberry pectin and anthocyanins, and hydrogen bond likely remained constant. Putative health benefits of anthocyanins are probably influenced by small pH and ionic strength changes in food matrixes. Graphical abstract: Image 1 Highlights: Binding sites and affinity of anthocyanins and blueberry pectins vary Anthocyanins bound more linear and more negatively charged pectin structure Increasing ionic strength weakens chelator fraction-anthocyanins interaction Decreasing pH strengthens hydrophobic or π-interaction of pectin-anthocyanins